Pengaruh Gaya Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Karyawan Di Kantor Desa Lolofaoso Nias Selatan - Waruwu, Priska Dini Yanti; Sihombing, Natalia E.; Sinaga, Kepler (Research and Community Service UNIVERSITAS KALBIS, 2024)
This study aims to evaluate the influence of Leadership Style and Work Discipline on Employee Performance at the Lolofaoso Village Office, South Nias. The research method used involves a survey of village officials and statistical data analysis to identify the relationship between the leadership style applied by the village head and the level of work discipline with individual performance results. The findings of this study are expected to provide strategic insights to companies to improve leadership effectiveness and encourage better work discipline in order to improve overall employee performance. This research was conducted using a qualitative method. Data collection techniques using a questionnaire. Based on the hypothesis testing with the t test, the t-test value was obtained 6.747> t table which was 1.989 and the significant value of the Leadership Style variable was 0.000 <0.05. So it can be concluded that Leadership Style has a positive and significant effect on Employee Performance at the Belawan Main Port Authority.